PENGARUH TERAPI RELAKSASI NAPAS DALAM TERHADAP PERUBAHAN TEKANAN DARAH PADA PASIEN LANSIA DENGAN HIPERTENSI DI PUSKESMAS PASUNDAN SAMARINDA - Rusni Masnina; Annaas Budi Setyawan (Jurnal Ilmu dan Teknologi Kesehatan, 2018)
The most common disease in the elderly are hypertension affected the heart and stroke. Treatment of hypertension a lifetime so it must be with non-pharmacological treatment, namely deep breathing relaxation. The aim of research to determine the effect of deep breath relaxation to changes in blood pressure of elderly patients with hypertension in the Health Center Pasundan. Using a quasi-experimental study, the design of two group pretest - posttest. The research sample of elderly hypertensive total of 32 people consisting of 16 samples dan16 experimental control samples. Data collection technique used purposive sampling. Univariate data using the mean value, median, standard deviation, maximum and minimum bivariate t test. Research resultthere are differences in systolic and diastolic blood pressure before and after the relaxation of airway in the experimental group and the control group (p value 0.001). There are differences in systolic and diastolic blood pressure before and after the relaxation of airway in the control group and the experimental group (p value 0.001). There is the influence of deep breaths relaxation therapy to changes in blood pressure where there is a significant difference (p value 0.001) and there was also a significant difference (p value 0.011).Conclusion No effect of relaxation therapy deep breath to changes in blood pressure of elderly patients with hypertension in the Health Center Pasundan Samarinda.